The fate of the nation-state - Seymour, Michel, 1954- (McGill-Queen's University Press, 2004)
Are Nation-states obsolete? Are multination states viable? Can we really create powerful supranational institutions? These are the questions that celebrated authors and specialists attempt to answer in this important collection of articles.